El Zeitgeist de la movilidad humana en tiempos de pandemia Trayectorias en directa y en reversa - Soledad Loyola Fuentes, M.; Boric Bargetto, Ljuba; Magaña Frade, Irene (Ariadna Ediciones, 2023)
To researchers and readers interested in migration issues. We present a set of works gathered under the title "The zeitgeist of human mobility in times of pandemic: direct and reverse trajectories. It is likely that the first The question that arises for the reader is the expression "zeitgeist". According to the RAE, it is an expression of the German language that It means "the spirit (Geist) of a time (Zeit)." It refers to intellectual and cultural climate of an era, "spirit of the age" or "spirit of the time". Indeed, as some studies have pointed out, "The COVID-19 pandemic is not only an unprecedented health emergency, but it is an economic and social emergency, the magnitude and consequences of which are having an impact "dramatic in the most vulnerable families." And by true, among migrant groups. Presented in this way, the topic is It is clear that the selected writings are appropriately inserted in this time characterized by the presence of the pandemic in different segments of the national population.